Time is Confidence: Monetary Incentives Metacognitive Profile on Duration Judgment - Mitra Taghizadeh Sarabi; Eckart Zimmermann (Journal of Cognition)
The question we addressed in the current study is whether the mere prospect of monetary reward gain affects subjective time perception. To test this question, we collected trial-based confidence reports in a task where participants made categorical decisions about probe durations relative to the reference duration. When there was a potential to gain a monetary reward, the duration was perceived to be longer than in the neutral condition. Confidence, which reflects the perceived probability of being correct, was higher in the reward gain condition than in the neutral condition. We found that confidence influences the sense of time in different participants. Participants with high confidence reported perceiving the duration signaled by the monetary gain condition longer than participants with low confidence. Our results showed that only high confidence individuals overestimated the context of monetary gain. Finally, we found a negative relationship between confidence and time perception, and that confidence bias at the maximum uncertainty duration of 450 ms is predictive of time perception. Taken together, the current study demonstrates that subjective measures of the confidence profile caused an overestimation of time rather than the outcome valence of reward expectancy.